Schools that have their own voice. Experiences of a self-evaluation process in 30 educational institutions - Barrientos Mollo, Roberto (2018)
The purpose of the research was to obtain a better understanding of the processes of school self-evaluation. To this end, an attempt was made to understand the experiences and perceptions of the main actors involved in an institutional self-evaluation process in which the possibility of a participative construction of the school model was offered, as well as the indicators and evaluation instruments of the same. This self-assessment process lasted two years and involved 30 schools of different educational levels and had the presence of a facilitator and an economic incentive from the regional government. The information was gathered from a survey and documentary review. The results of the study showed that people are open to collaborate and be part of self-evaluation processes. Furthermore, the figure of external support for the development of capacities is necessary. It was also discovered that the economic incentive is an element that can contribute to the initial adoption, however there is a risk of generating dependency on this extrinsic motivation